The politics of power and society in the face of epidemics and famines in the province of Algeria during the 18-19 century AD - yousfi, sarhouda (The Algerian Historical Journal, 2026)
This study aims to identify the policy of the regency of Algeria in times of epidemics and famines, from a set of documents, which inform us about the modes of transmission of epidemics in Algeria and the way of to face. an economic policy based on the reduction of grain exports. As for society, it resorts to solidarity and opens landfills to distribute food to the needy. Epidemics have affected demographics, and fear of infection drives people to flee from population centers to the mountains, impacting socio-economic movement. Periods of epidemics are followed by famines which lead to high commodity prices and food shortages, and this is what led to the importation of grain from the Ottoman Empire